Sequencing anoxic/anaerobic membrane bioreactor (SAM) pilot plant for advanced wastewater treatment - Cho, JW; Song, KG; Lee, SH; Ahn, KH (ELSEVIER SCIENCE BV, 2005)
The performance of the sequencing anoxic/anaerobic membrane bioreactor process (SAM) was investigated in a pilot-scale experiment. The constant flux was maintained and the variation of the transmembrane pressure was monitored to evaluate the membrane fouling. The municipal wastewater was continuously fed into the SAAR with a flow rate of 72 m(3)/d and 50 m(3)/d for 45 days and 65 days, respectively. The membrane flux was maintained at 15.4 L/m(2)/h to treat the influent of 72 m(3)/d and 12 L/m(2)/h for 56 m(3)/d. The anoxic condition for denitrification was provided for 3 h during a cycle of 4 h with the internal recycle. The anaerobic condition for phosphorus release was maintained for I h during the cycle of 4 h without internal recycling. This operation mode would result in more efficient use of the organic substrate in the influent for the nitrogen removal. The results show that the flux of less than 12 L/m(2)/h is desirable to prevent serious membrane fouling compared to 15.4 L/m(2)/h. Decreasing the flux by 22% retarded the membrane fouling and prolonged the operation time by 31%. In the short hydraulic retention time (HRT) and high flux condition, the nutrient removal efficiency increased compared to the long HRT and low flux condition. Increasing HRT by 30% resulted in a decrease of nutrient removal efficiency by 10%. However, the short HRT and high flux condition resulted in the acceleration of membrane fouling. One feasible solution to this problem is to add more modules of membranes to meet the high HRT condition without increasing membrane flux.